2020
DOI: 10.33306/mjssh/81
|View full text |Cite
|
Sign up to set email alerts
|

Tahap Pengetahuan Guru Bahasa Arab Dalam Melaksanakan Kelas Berbalik [The Level of Knowledge Arabic Language Teachers in Implementing Flipped Classroom]

Abstract: The use of technology in education is very common nowadays, and it is strongly encouraged as it provides effectiveness of the teaching and learning process especially through the 'Flipped Classroom' method. The form of this method focuses on the uses of technology and student-centered. Previous studies have shown that the Flipped classroom method has a positive effect on increasing students' interest in learning. However, recent studies show that most Arabic language teachers still use traditional meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The teaching of adjectives based on the flipped classroom approach is perceived positively by the study participants. 13 Hilmi et al (2020) This study assessed the knowledge Arabic language teachers need to master to effectively implement the flipped classroom approach.…”
Section: Findings Of the Studymentioning
confidence: 99%
“…The teaching of adjectives based on the flipped classroom approach is perceived positively by the study participants. 13 Hilmi et al (2020) This study assessed the knowledge Arabic language teachers need to master to effectively implement the flipped classroom approach.…”
Section: Findings Of the Studymentioning
confidence: 99%
“…As such, study [8] identified that teachers are the most accurate and responsible individual to implement this transformation in their teaching. This includes integrating technological advances in the teaching of Arabic.…”
Section: Introductionmentioning
confidence: 99%